The Development of Biotechnology Textbook with Jember Local Wisedom for Students at Fourth Grade of Elementary School - Ine Febrianti; Agustiningsih Agustiningsih; Kendid Mahmudi; Nuriman Nuriman; Singgih Bektiarso (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
This research aims to develop a teaching material in the form of Biotechnology Textbooks with Jember Local Wisdom for Grade IV at Elementary Schools. This type of research is development research using the Borg and Gall model which consists of 10 stages. The quality aspects of t Biotechnology Textbooks with Jember Local Wisdom were validity and effectiveness. The subjects of this research trial were grade IVA students of Public Elementary School 3 of Kepatihan, grade IVA students and IVB Public Elementary School 4 of Kebonsari. Data collection methods in this study used a questionnaire, tests, and validation. Based on the results of data analysis, it was found that biotechnology-based textbooks for local wisdom in Jember were declared very valid with a percentage of validity of 90.6%. The effectiveness of textbooks is known from the percentage of student learning outcomes of, 80.9%, 81.5%, and 84.6%. Textbooks are also categorized as having a positive response with a percentage of 91.5%, 94.6%, and 97%. Based on the results of the analysis of the data it can be concluded that the textbook has been declared to be very valid and very effective and received positive responses from students so that the Biotechnology Textbooks with Jember Local Wisdom can become a learning medium in schools.